Legal reform to enhance global text and data mining research - Fiil-Flynn, Sean M.; Butler, Brandon; Carroll, Michael; Cohen-Sasson, Or; Craig, Carys; Guibault, Lucie; Jaszi, Peter; Jütte, Bernd Justin; Katz, Ariel; Quintais, João Pedro; Margoni, Thomas; de Souza, Allan Rocha; et al. (Science (American Association for the Advancement of Science), 2022)
Outdated copyright laws around the world hinder research Researchers engaged in text and data mining (TDM) research collect vast amounts of digitized material and use software to analyze and extract information from it. TDM is a crucial first step to many machine learning, digital humanities, and social science applications, addressing some of the world’s greatest scientific and societal challenges, from predicting and tracking COVID-19 to battling hate speech and disinformation ( 1 – 3 ). Although applications of TDM often occur across borders, with researchers, subjects, and materials in more than one country, a patchwork of copyright laws across jurisdictions limits where and how TDM research can occur. With the World Intellectual Property Organization (WIPO) Standing Committee on Copyright and Related Rights, and legislatures around the world, deliberating the harmonization of copyright exceptions for various research uses, we discuss policy measures that can ensure that TDM research is unambiguously authorized under copyright law.